2018
DOI: 10.21608/puj.2018.7662
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a deworming campaign by albendazole during 2016 in a rural area of Giza Governorate, Egypt

Abstract: Background: Egypt carried out the first national deworming campaign in 2016 targeting two million school-age children. The control program was led by the Endemic Diseases Department of the Egyptian Ministry of Health and Population (MOHP), in collaboration with the WHO Office in Egypt. Endemic Diseases Control Administration of Giza Governorate selected Tamwah village for the present work to represent the rural areas of Giza Governorate. The campaign targeted children from the first grade of primary schools ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…There are several studies on the evidence for zoonosis due to giardiasis, the disease was identified as a prevalent protozoan infection in the children, with an infection rate of 24% (21) in Egypt. The low frequency of helminth parasites in Egypt is due to the availability of deworming drugs and campaigns (22).…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies on the evidence for zoonosis due to giardiasis, the disease was identified as a prevalent protozoan infection in the children, with an infection rate of 24% (21) in Egypt. The low frequency of helminth parasites in Egypt is due to the availability of deworming drugs and campaigns (22).…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted by Cholifah (2016) also showed similar results: The percentage of pinworm infections was higher in those who had never taken medicine or who took worm medicine for >6 months than in those who took medicine for <6 months. Another study conducted by Dahesh (2018) showed that children given albendazole showed negative results from eggs or adult Enterobius vermicularis worms. Similar results were revealed by Suraweera, Galgamuwa, Iddawela, & Wickramasinghe (2015) that the consumption of anthelmintic is able to prevent pinworm infections, but this needs to be repeated two to three times at intervals of three weeks.…”
Section: Discussionmentioning
confidence: 99%